Pro-WEAI - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
WEAI was developed during Phase I from a project, led by IFPRI and part of the PIM portfolio. The stage was incorrectly entered in 2017 and is now considered stage 3.